Avaliação da aprendizagem em processo: usos dos resultados pelos professores de Língua Portuguesa e Matemática dos anos finais do Ensino Fundamental - Santos, Vilma Claro dos (2017)
This research deals with the Assessment of Learning in Process (ALP), that has a diagnostic nature. It is applied by the Education Department of the State of São Paulo to public school students. The purpose of this paper is to understand the objectives of the ALP and the factors that contribute or do not contribute to the use of its results by Portuguese and Mathematics teachers of the final years of elementary education. The research, that has a qualitative approach, is divided in two stages: analysis of official documents that guide the development process of the ALP and interviews with two teachers of Portuguese Language, two teachers of Mathematics and a coordinating teacher of a public state school located in Guarulhos. Documentary research was carried out within the scope of the Education Department of the State of São Paulo, the Teaching Department of Guarulhos – North, and the school unit, which is the locus of this investigation. The semi-structured interviews were recorded and transcribed. Data analysis and interpretation were based on two categories: ALP goals and uses of ALP results. Through the analysis of the collected data it was possible to infer some ALP weaknesses, for example, the non-participation of the actors of the school when ALP was implemented, the loss of the diagnostic nature of ALP, which walks beside the official curriculum, the short time for debates between coordinating teachers during the teacher‟s education, and the use of the results as grade by the teachers